Confocal Raman spectroscopic study of melt inclusions in olivine of mantle xenoliths from the Bultfontein kimberlite pipe (Kimberley cluster, South Africa): Evidence for alkali‐rich carbonate melt in the mantle beneath Kaapvaal Craton. (13th July 2021) - Sharygin, Igor S.; Golovin, Alexander V.; Tarasov, Alexey A.; Dymshits, Anna M.; Kovaleva, Elizaveta
Abstract: Identifying the composition of primary/primitive mantle melts is crucial for understanding the mantle's evolution and mantle‐derived magmatism. Melt inclusions in mantle xenoliths provide key information about such melts. This study used confocal Raman spectroscopy to characterize mineral assemblage of unexposed crystallized secondary melt inclusions in the olivine from the xenoliths of the sheared garnet peridotites from the Bultfontein kimberlite pipe (Kimberley cluster, Kaapvaal Craton, South Africa). The studied peridotites originated from 112‐ to 146‐km mantle depths. In total, 16 minerals were identified among daughter crysatls, which include carbonates (calcite, magnesite, dolomite), alkali carbonates (eitelite, nyerereite, gregoryite/natrite, K–Na–Ca–carbonate (K, Na)2 Ca(CO3 )2 (K analogue of nyerereite), alkali carbonates with additional anions (northupite, bradleyite, burkeite), alkali sulfates (glauberite, thenardite, aphthitalite), apatite, tetraferriphlogopite, and magnetite. Several more daughter minerals gave distinct Raman spectra, but they were not determined due to the lack of similar spectra in the databases. Carbonates are predominant among the daughter minerals in the melt inclusions. Many daughter minerals are rich in alkalis. These facts indicate that melt(s), parental for the inclusions, is alkali‐rich carbonate in composition. Two possible models were suggested for the origin of these melt inclusions: (1) in situ fracturing of olivine and the mantle melt infiltration shortly before the sheared peridotites were entrained by the ascending kimberlitic magma; (2) infiltration of the transporting kimberlite melt into xenoliths during ascent. Both models imply that the alkali‐rich carbonate melt(s) that interacted with peridotites originated at a greater depth than the entrapment level of studied xenoliths (>150 km), that is, at the base of the lithosphere or in the asthenosphere. This melt is genetically related to the kimberlite magmatism that formed the Bultfontein pipe and points at the alkali‐rich carbonate composition of primary kimberlite melt. Abstract : Olivine‐hosted secondary crystallized melt inclusions from sheared peridotite xenoliths from the Bultfontein pipe (Kimberley cluster, Kaapvaal Craton, South Africa) were studied using confocal Raman spectroscopy. Sixteen minerals were identified among the daughter phases in the inclusions, namely, calcite, magnesite, dolomite, eitelite, nyerereite, gregoryite/natrite, (K, Na)2 Ca(CO3 )2, northupite, bradleyite, burkeite, glauberite, thenardite, aphthitalite, apatite, tetraferriphlogopite, and magnetite. These inclusions are "snapshots" of Cl–S–alkali‐rich carbonate melt that originated at the base of the lithosphere or in the asthenosphere.